OPTIMALISASI POTENSI LOKAL MELALUI PENGUATAN BRANDING MINYAK KELAPA DO KORLEKO SELATAN: OPTIMALISASI POTENSI LOKAL MELALUI PENGUATAN BRANDING MINYAK KELAPA DO KORLEKO SELATAN - Yadnya, Made Sutha; Haeki Manzis; Nanda Febriyani Putri; Miranti Wulan Saputri; Roro Ranti Dea Alfathya; Risna Putri Zahara; Nur Ariza Kurnia Dewi; Lalu Diandra Surya Wardhana; Dwi Lestari; Baiq Faridha Aulya Maharani; Elsya Mayori; Nabilah Putri Nursuha (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The coconut oil branding enhancement program in Korleko Selatan Village, East Lombok, was implemented to optimize local potential and increase the competitiveness of coconut-based products. Despite its abundant coconut resources, the village’s utilization of this commodity has been limited to small-scale traditional processing without clear brand identity, standardized packaging, or effective marketing strategies. Through a 45-day program of potential surveys, training, and community mentoring—particularly targeting women’s household groups—participants were equipped with skills in brand identity development, packaging design, digital marketing, and the use of QR Code technology for production process transparency. The program resulted in the creation of “Koska Coconut Oil,” featuring labeled packaging that reflects local identity while meeting hygiene and aesthetic standards. The adoption of digital marketing via social media and online marketplaces is expected to expand market reach, including potential export opportunities. This initiative not only increases product value and community income but also strengthens local cultural identity and inspires the development of other coconut-derived products. The program’s success demonstrates that participatory branding strategies can serve as an effective tool for sustainable village economic development.